Bilddenken und Morphologie Interdisziplinäre Studien über Form und Bilder im philosophischen und wissenschaftlichen Denken - Follesa, Laura; Vercellone, Federico (De Gruyter, 2021)
What is the relationship between "image" and human thinking? What is the role of the concept of "form" in human knowledge? Scholars from the fields of philosophy, cultural studies, the history of science, aesthetics, literature, anthropology, mathematics, and biology take historical and theoretical approaches to investigate the connection between the activity of thinking and concepts of image and form.